Optimalisasi Layanan Rumah Edukasi Berbasis QR Digital Perpustakan untuk Peningkatan Literasi Masyarakat - Risky Surya K; M. Syahril Mubarok; Nikmatul Wafiyah; Ifroh Aisah A; Novita Ayu T; Devi Nur Rohma; Ayu lailatus Zakiya; Safinatun Najah; Nurhidayat (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The low reading interest and limited access to literacy remain major challenges in rural communities. Penambangan Village, through the Rumah Edukasi (Education House), strives to provide more effective literacy services by utilizing digital technology. This study aims to optimize the Rumah Edukasi services through a QR Digital Library as a means of improving community literacy. The research employed the Participatory Action Research (PAR) method, actively involving the community in the design, implementation, and evaluation of the program. The service implementation was carried out by providing digital reading collections accessible via QR codes placed at various strategic points in the village. The findings indicate that the application of the QR Digital Library successfully increased public access to reading materials, expanded literacy outreach, and fostered a more flexible and independent reading culture. In conclusion, the optimization of QR-based digital services has proven to be an innovative solution for strengthening the literacy ecosystem at the village level, while also serving as a model for the development of technology-based literacy services in rural communities.